Pelacakan Virus Bercak Putih pada Udang Vaname (Litopenaeus vannamei) di Lombok dengan Real-Time Polymerase Chain Reaction (DETECTION OF WHITE SPOT SYNDROME VIRUS IN LITOPENAEUS VANNAMEI IN LOMBOK ISLAND USING REAL-TIME POLYMERASE CHAIN REACTION) - Arafani, Lulu; Ghazali, Mursal; Ali, Muhamad (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
White spot syndrome virus (WSSV) is one of the most threatening diseases in shrimp and othercrustaceans affecting global shrimp farming. Since firstly detected in Taiwan in 1992, the disease hasspread globally and followed with considerable socio-economic consequences. This research was performedto detect the WSSV infection in shrimp farming in Lombok Island’s (West Nusa Tenggara) using real-timepolymerase chain reaction. Samples of vaname (Litopenaeus vannamei) were collected from several shrimpfarming in Lombok. Results indicated that the spread of WSSV has reached shrimp farms in Lombok,especially in Lendang Jae, West Lombok. Therefore, a biosurveillance program is strongly recommendedto government to avoid and halt the spread of the disease in East Indonesia region .
Keywords: WSSV; Litopenaeus vannamei; RT-PCR